The Campanian stage - Hancock, J; Gale, A; Gardin, S; Kennedy, W; Lamolda, M; Matsumoto, T; Naidin, D (1996)
The Campanian working party in Brussels did not wish to make a conclusive recommendation but there was a strong feeling that the base of the stage should be fixed at the extinction-level of the crinoid Marsupites. Other criteria discussed included ammonites, belemnites, foraminifera, calcareous nannofossils and magnetostratigraphy. Candidates for a boundary-stratotype occur in central Texas and south-east England. Until these sections have been described in detail, it will not be possible to choose a boundary-stratotype, and hence make a firm recommendation to the International Subcommission for the base of the stage. It was felt that three substages should be used for the Campanian, but international correlations within the stage are still too uncertain to make recommendations for the definitions of these substages.